Hospitalisation in the last month of life and in-hospital death of nursing home residents: a cross-sectional analysis of six European countries - Yvonne Engels; Sheila Payne; Bregje D Onwuteaka-Philipsen; Paula Andreasen; Lieve Van den Block; Giovanni Gambassi; Tinne Smets; Violetta Kijowska; Katarzyna Szczerbińska; Lara Pivodic; L Deliens; Eddy Adang; et al. (BMJ Open)
Objectives To examine the rate and characteristics of hospitalisation in the last month of life and place of death among nursing home residents and to identify related care processes, facility factors and residents’ characteristics.Setting A cross-sectional study (2015) of deceased residents in 322 nursing homes in six European countries.Participants The nursing home manager (N=1634), physician (N=1132) and primary nurse (N=1384) completed questionnaires.Outcome measures Hospitalisation and place of death were analysed using generalised linear and logistic mixed models. Multivariate analyses were conducted to determine associated factors.Results Twelve to 26% of residents were hospitalised in the last month of life, up to 19% died in-hospital (p<0.001). Belgian residents were more likely to be hospitalised than those in Italy, the Netherlands and Poland. For those dying in-hospital, the main reason for admission was acute change in health status. Residents with a better functional status were more likely to be hospitalised or to die in-hospital. The likelihood of hospitalisation and in-hospital death increased if no conversation on preferred care with a relative was held. Not having an advance directive regarding hospitalisations increased the likelihood of hospitalisation.Conclusions Although participating countries vary in hospitalisation and in-hospital death rates, between 12% (Italy) and 26% (Belgium) of nursing home residents were hospitalised in the last month of life. Close monitoring of acute changes in health status and adequate equipment seem critical to avoiding unnecessary hospitalisations. Strategies to increase discussion of preferences need to be developed. Our findings can be used by policy-makers at governmental and nursing home level.